A dual-mode hydrogen peroxide and kerosene space propulsion system pressurized by electric pumps. Issue 1 (1st May 2022) - Zhou, Chuang; Yu, Nanjia; Li, Tianwen; Gong, Haojie
Abstract: In this study, the performance characteristics and previous application cases of the dual-mode propulsion system (DMPS) were discussed. Besides, a dual-mode hydrogen peroxide and kerosene space propulsion system pressurized by electric pumps was proposed via the analysis of the existing problems with respect to the dual-mode propulsion system. In addition, the working process of this system was analyzed by system modeling and simulation. Further, the feasibility of DMPS was verified by exploring the working characteristics of the bipropellant main thruster and the monopropellant attitude control thruster. As per the analysis results, the DMPS proposed in this study contributed to eliminating the problems in the application of the dual-mode propulsion system at the present stage, and it also provided effective guidance in improving the performance of the propulsion system, adjusting the thrust flow rate, and making the propellant non-toxic.